The Influence of Ultrasonic Vibration Milling on the Surface Integrity of 3D Printed TA15 - Wei, Jun; Zhu, Xueming (International Journal of Mechanical and Electrical Engineering, 2025)
Ultrasonic assisted milling technology has shown significant effects in improving the quality of machined surfaces. During ultrasonic milling, while maintaining the same cutting time, changes in the axial ultrasonic vibration amplitude of the tool can cause changes in the height of the surface microstructure contour, which in turn affects the microstructure. Based on the above reasons, different machining surface microstructures can be obtained by changing the axial ultrasonic amplitude of the tool. This article mainly uses surface morphology, hardness, and surface roughness as key indicators to evaluate the integrity of the machined surface. It systematically analyzes the trends and laws of the influence of ultrasonic amplitude and feed rate per tooth on surface morphology, surface hardness, and surface roughness in the process of ultrasonic vibration milling SLM forming TA15 titanium alloy.